2002
DOI: 10.1200/jco.2002.08.121
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Survival in Adult Patients With Cerebral Low-Grade Glioma

Abstract: P r o g n o s t i c F a c t o r s f o r S u r v i v a l i n A d u l t P a t i e n t s W i t h C e r e b r a l L o w -G r a d e G l i o m aPurpose: To identify prognostic factors for survival in adult patients with cerebral low-grade glioma (LGG), to derive a prognostic scoring system, and to validate results using an independent data set.Patients and Methods: European Organization for Research and Treatment of Cancer (EORTC) trial 22844 and EORTC trial 22845 are the largest phase III trials ever carried out in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
474
5
14

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 828 publications
(525 citation statements)
references
References 30 publications
32
474
5
14
Order By: Relevance
“…The cutoff value of 40 years was chosen based on the median age of the study population (34 years) and on recently reported results from a series of patients with low-grade glioma. 32,33 Age was not identified as a prognostic factor by Guyotat et al, 15 who chose a different cutoff point; Guyotat et al actually observed a difference in survival that was similar to the one reported in the current series (16%), but the difference was not statistically significant, probably due to the limited number of patients or the lack of stratification. In the series investigated by Guyotat et al, 15 older patients had a higher rate of infratentorial tumors, Grade 2 histology, and macroscopic total resection compared with younger patients; these characteristics confounded the impact of age on survival.…”
Section: Prognostic Factorssupporting
confidence: 57%
“…The cutoff value of 40 years was chosen based on the median age of the study population (34 years) and on recently reported results from a series of patients with low-grade glioma. 32,33 Age was not identified as a prognostic factor by Guyotat et al, 15 who chose a different cutoff point; Guyotat et al actually observed a difference in survival that was similar to the one reported in the current series (16%), but the difference was not statistically significant, probably due to the limited number of patients or the lack of stratification. In the series investigated by Guyotat et al, 15 older patients had a higher rate of infratentorial tumors, Grade 2 histology, and macroscopic total resection compared with younger patients; these characteristics confounded the impact of age on survival.…”
Section: Prognostic Factorssupporting
confidence: 57%
“…Another limitation is that our study lacks results regarding the predictive role of age, sex, tumor volume, and treatment protocols. Our choice not to analyze these parameters was justified by the small population size (the significance level of the multiple regression analysis including all these factors was P ϭ .08) and the diverse results found regarding age and sex in the literature, 11,17 whereas the predictive role of different treatment protocols has been demonstrated in recent larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…10,17 It was recently shown that rCBV may be able to distinguish the stable from the rapidly progressing gliomas among patients with the same histopathologic grade (WHO grade II). 10 Considering the results from 2 previous studies, 7,10 we conducted an investigation that included all patients with primary brain tumors, with the histologic diagnosis of glioma as the only requirement.…”
Section: Discussionmentioning
confidence: 99%
“…16 This relationship is perhaps best exemplified by the fact that patients with LGG rarely present with neurological deficits. 36 Moreover, mapping studies in patients with LGG demonstrate multiple patterns of reorganization and compensation, including identifying function persisting within the tumor or redistributed immediately around the tumor, throughout the ipsilateral hemisphere, or into the contralateral hemisphere. 16 In all cases, patients seemingly have no deficit.…”
Section: Disease-related Functional Variabilitymentioning
confidence: 99%